HEDONIC PRICE ANALYSIS OF CHICKEN MEAT CUT IN BAUCHI STATE, NIGERIA - Hamidu, B.; Mohammed, I.; Murtala, N.; Jibril, S. A.; Mohammed, S. Y. (Journal of Agripreneurship and Sustainable Development, 2021)
The study examined the Hedonic price analysis of chicken meat cut in Bauchi State, Nigeria. A multi-stage sampling procedure was used to select 586 households in the study area and data were collected through the use of structured questionnaire. The data were analysed using descriptive and inferential statistics. The results of the study revealed that most (96.9%) of the household heads were male and married (89.8%) with about 35.7% of them having secondary education and 30.0% take farming as their occupation. The study also revealed the mean age, mean household size and mean monthly household head income as 41 years, 8 person per household and N47,481.46, respectively. The results of the hedonic regression analysis revealed that, age of the household head, sex of chicken, types of chicken breed, marital status and market locations were the major factors influencing the price of chicken in the study area. The major constraints to chicken consumption were financial problem, high cost of chicken, health related problems, poor sanitary condition of meat vendors as well as high prices of other food items of necessities. It was therefore recommended that, federal/State governments should enhance economic boasting programmes to improve the income of consumers; there should be a concerted effort on the part of government and non-governmental bodies on measures of increasing animal feeds and feeding to boast animal production. More study also needs to be done on segmentation and differentiation of chicken meat cuts based on international standard.